The relationship between professional ethics and organizational commitment of faculty members in Kurdistan University of Medical Sciences - Sheikhzakaryaie, Neda; Atashzadeh-Shoorideh, Foroozan (Advances in Nursing & Midwifery, 2016)
Abstract: Background and Aim: Organizational commitment and professional ethics are two of the most important issues in higher education. The commitment to these issues is very challenging for the faculty members. The aim of this study was to investigate the relationship between professional ethics and organizational commitment of faculty members. Materials and Methods: This was a descriptive-correlative study. The sample consisted of 150 faculty members of Kurdistan University of Medical Sciences, they were randomly selected. The data selection tools were three questionnaires including demographic work ethics and organizational commitment questionnaires. Data was analyzed by Pearson correlation and single-sample t test using SPSS (V. 16). Results: The mean score of professional ethics was 6.06 ± 1.05 and the mean score of organizational commitment was 4.26 ± 1.10 which were above average of 4. The scores of professional ethics and organizational commitment dimensions were also higher than average. There was a significant relationship between professional ethics and organizational commitment and their dimensions (P<0. 05, r=0. 12). Conclusion: According to the findings, more attention to ethical standards and promotion of them among faculty members is necessary. This is the responsibility of the managers of higher education institutions. Keywords: Professional Ethics; Ethics, Institutional; Faculty